Cost-Effective Tissue Culture Protocols for Neglected Indigenous Dioscorea Varieties: Optimization of Disinfection, Browning Control, and Growth Enhancement - Sookruksawong, Suchonma; Pilahome, Warisa (Trends in Sciences, 2025)
Indigenous Dioscorea species are important neglected and underused species (NUS) that represent rich genetic resources for food security and medicinal applications, offering exceptional climate resilience and nutritional diversity crucial for sustainable agriculture. However, their propagation is hampered by expensive tissue culture techniques and high equipment expenses. The study optimized disinfection techniques, browning control, and growth promotion to develop comprehensive low-cost tissue culture procedures for purple- and white-fleshed indigenous Dioscorea varieties. Nodal explants were examined with commercial bleach (5% - 20%) for surface disinfection, polyvinylpyrrolidone, PVP (0 - 1,500 mg/L) for browning management, hormone combinations (BA and NAA at 0.5 - 2.0 mg/L) for morphogenesis, and alternative medium disinfection methods (bleach 0.5 - 4.0 mL/L versus autoclaving). Optimal explant disinfection was achieved using 10% commercial bleach, resulting in 67% - 73% survival at a cost of 0.117 THB (Thai Baht) per surviving plant. PVP at 1,000 mg/L substantially suppressed browning while increasing survival to 80% in white-fleshed and 67% in purple-fleshed varieties, with white-fleshed varieties regularly outperforming, purple-fleshed variants. BA at 2.0 mg/L increased shoot growth (5.87 shoots per explant), while NAA at 1.0 mg/L increased root formation (5.89 roots per explant). Bleach-based medium disinfection at 1 - 2 mL/L achieved autoclaving performance while substantially lowering equipment investment from 60,000 to 2,500 THB. These integrated protocols establish complete low-cost tissue culture systems utilizing commercial bleach for all disinfection steps, eliminating expensive laboratory equipment requirements and enabling community-based propagation systems for indigenous Dioscorea conservation in resource-constrained environments. HIGHLIGHTS 10% commercial bleach for explant disinfection achieved 67% - 73% survival with minimal contamination. PVP at 1,000 mg/L prevented browning with genotype-specific responses. BA 2.0 mg/L and NAA 1.0 mg/L optimized shoot and root development. Bleach-based medium disinfection reduced equipment costs from 60,000 to 2,500 THB. Low-cost protocol enabled Dioscorea tissue culture and conservation. GRAPHICAL ABSTRACT